EFEKTIVITAS PENERAPAN ANDRAGOGI DALAM PROGRAM EDUKASI INDEKS ZAKAT NASIONAL (IZN)-BAZNAS - SULISTYOWATI SULISTYOWATI; ASRI NOER RAHMI (JURNAL PENDIDIKAN ISLAM AL-ILMI, 2018)
Abstract: The study aims to analyze the effectiveness of Adragogy implementation of National Zakat Index (NZI) by National Zakat Board (BAZNAS)’s socialization. This descriptive qualitative-explorative analysis took In-depth interviews to BAZNAS and lecturers for getting primary data. Secondary data obtained through the Desk Study in the form of exploration of references from various scientific sources. The results of the study are: Firstly, The practice of andragogy in various countries has different focus depend on the objectives to be achieved; Secondly, Public literacy and zakat stakeholders increases along with the zakat conscious movement by BAZNAS; Thirdly, The adoption of Andragogy in the education of NZI has a tendency to Bloom's Taxonomy Cognitive Domain. Discussions and recommendations based on the results of the research in the form of: First, Andragogy learning theory in general is still a concern with attention to systematics, stages and rules that need to be obeyed; Second, The application of Andragogy in the process of education of NZI is effective but still needs to increase creativity by utilizing the media of IT sophistication which also targets the focus on millenials person and extends the scope of objects to unreached areas; Third, the authors propose a new scheme in the form of the National Zakat-Wakaf Integration Index (NZWI) model as a form of synergy between zakat and waqf involving two government boards namely BAZNAS and Indonesian Waqf Agency (BWI) for higher success in the future. Keywords: Andragogy, Efectiveness, National Zakat Index (NZI), Education